2004
DOI: 10.2528/pier04021905
|View full text |Cite
|
Sign up to set email alerts
|

Low-Frequency Solution for a Perfectly Conducting Sphere in a Conductive Medium With Dipolar Excitation

Abstract: Abstract-This contribution concerns the interaction of an arbitrarily orientated, time-harmonic, magnetic dipole with a perfectly conducting sphere embedded in a homogeneous conductive medium. A rigorous low-frequency expansion of the electromagnetic field in positive integral powers (jk) n , k complex wavenumber of the exterior medium, is constructed. The first n = 0 vector coefficient (static or Rayleigh) of the magnetic field is already available, so emphasis is on the calculation of the next two nontrivial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 11 publications
0
27
0
Order By: Relevance
“…In a previous paper [16], for the sphere case, the authors have shown that low-frequency (LF) expansions can be used and applied to fields and quantities involved. All of the scalar or vectors are written as summations in terms of powers of (jk), where k is the wave number in the surrounding medium and j is the complex number satisfying j 2 = −1.…”
mentioning
confidence: 99%
“…In a previous paper [16], for the sphere case, the authors have shown that low-frequency (LF) expansions can be used and applied to fields and quantities involved. All of the scalar or vectors are written as summations in terms of powers of (jk), where k is the wave number in the surrounding medium and j is the complex number satisfying j 2 = −1.…”
mentioning
confidence: 99%
“…The efficiency of the model can be successfully demonstrated via the degeneration of the ellipsoidal shape and the reduction of the present results to the already known spheroidal [10] and spherical [7] analogous, since effective formulae of limiting procedures are given. On the other hand, the obtained analytical results are presented suchlike so as a numerical method could be employed furtherly as a continuation of this project.…”
Section: Introductionmentioning
confidence: 79%
“…On the other hand, by virtue of the previous analysis about the reduction rules to the spheroidal or to the spherical geometry, the manipulation of our main results for the electromagnetic fields H 0 , H 2 , H 3 , E 1 , and E 3 in the domain Ω ≡ (R 3 ) − {r 0 } given in (58) is a straightforward task and leads to recovering the corresponding and already known results from the literature, described earlier in the Introduction section for a spheroidal [10] and a spherical [7] nonpenetrable scatterer.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To calculate the target response, we avoid time-consuming spherical harmonic formulations [27] and begin with the simple parametric approximation presented by [28] for estimating the timedomain B field response of a conductive permeable sphere due to a step function excitation. This is also the electro-dynamic ALLTEM response since its excitation is integral of the step (i.e., a triangle wave), it uses dB /dt receivers, and the integral and derivative operations cancel each other.…”
Section: Signalmentioning
confidence: 99%